2005
DOI: 10.1063/1.2143131
|View full text |Cite
|
Sign up to set email alerts
|

Strong green upconversion emission in ZrO2:Yb3+–Ho3+ nanocrystals

Abstract: Structural and upconversion emission properties of ZrO2:Yb3+–Ho3+ nanocrystals were analyzed as function of Yb3+ concentration. Structural characterization shows a crystallite size up to 80 nm and tetragonal and cubic phase as the main crystalline structures. Strong green (540 nm) and weak red (670 nm) and near infrared (760 nm) emission bands were observed with 968 nm excitation. The upconversion is based on two photons absorption either by the energy transfers from Yb3+ ion or by the excited state absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…This is a very significant step towards the advance of materials with substantial application potential for luminescent markers, imaging, and displays. De La Rosa et al [101] reported green UC emission in ZrO 2 :Yb 3 + ,Ho 3 + nanocrystals. Strong green (l = 540 nm) and weak red (l = 670 nm) and near infrared (l = 760 nm) emission bands were obtained after excitation at l = 968 nm.…”
Section: Co-dopingmentioning
confidence: 98%
“…This is a very significant step towards the advance of materials with substantial application potential for luminescent markers, imaging, and displays. De La Rosa et al [101] reported green UC emission in ZrO 2 :Yb 3 + ,Ho 3 + nanocrystals. Strong green (l = 540 nm) and weak red (l = 670 nm) and near infrared (l = 760 nm) emission bands were obtained after excitation at l = 968 nm.…”
Section: Co-dopingmentioning
confidence: 98%
“…Higher upconversion efficiencies have been achieved in materials co-doped with Yb 3+ and Ho 3+ , where Yb 3+ acts as a sensitizer for Ho 3+ owing to its strong absorption around 980 nm. 28,29 Oxides materials have been reported as suitable host for Ho 3+ upconversion. 30,31 In the present work, we present results obtained on a new upconversion material, namely Ln 2 BaZnO 5 : Yb 3+ , Ho 3+ (Ln=Y,Gd).…”
Section: Introductionmentioning
confidence: 99%
“…Patra et al investigated the effect of crystal size and crystal phase on UC luminescence in ZrO 2 : Er 3+ nanocrystals [10]. In relevant literatures, the UC samples were synthesized by chemical methods, such as solgel [10,11], coprecipitation [12], solution combustion [13,14], and controlled hydrolysis synthesis procedures [14]. In these chemical methods, the contamination caused by chemical precursors or additives may lead to the change of the UC dynamics and affect the UC luminescence results, especially in the nanomaterials [12,13].…”
Section: Introductionmentioning
confidence: 99%